2013
DOI: 10.1242/jcs.132845
|View full text |Cite
|
Sign up to set email alerts
|

Fission yeast nucleolar protein Dnt1 regulates G2/M transition and cytokinesis through downregulating Wee1 kinase

Abstract: There was an error published in J. Cell Sci. 126, 4995-5004.One source of funding was accidentally omitted. The correct funding section is as shown below. FundingThis work was supported by the National Institutes of Health [grant number Summary Cytokinesis involves temporally and spatially coordinated action of the cell cycle, cytoskeletal and membrane systems to achieve separation of daughter cells. The septation initiation network (SIN) and mitotic exit network (MEN) signaling pathways regulate cytokinesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…1A). This strategy was employed to monitor the abundance of Wee1 protein because it has been used reliably in previous studies (Keifenheim et al, 2017;Yu et al, 2013). Strikingly, our quantitative measurements indicated that Wee1 was significantly stabilized in the pof3Δ and pof1-6 mutants, but not in the other F-box protein deletion mutants examined (Fig.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…1A). This strategy was employed to monitor the abundance of Wee1 protein because it has been used reliably in previous studies (Keifenheim et al, 2017;Yu et al, 2013). Strikingly, our quantitative measurements indicated that Wee1 was significantly stabilized in the pof3Δ and pof1-6 mutants, but not in the other F-box protein deletion mutants examined (Fig.…”
Section: Introductionmentioning
confidence: 64%
“…G418 disulfate (Sigma-Aldrich), hygromycin B (Sangon Biotech) or nourseothiricin (clonNAT; Werner BioAgents) was used at a final concentration of 100 μg/ml where appropriate. Serial-dilution drop tests for growth were performed as previously described (Yu et al, 2013).…”
Section: Fission Yeast Strains Media Chemicals Genetic Methods Andmentioning
confidence: 99%
See 2 more Smart Citations
“…The processes of the Cdk1 phosphorylation and dephosphorylation are mediated by the nuclear kinase Wee1 and the dual-specificity phosphatase Cdc25 (Harvey et al, 2005). Wee1 can delay mitosis by inhibiting the Cdk1 phosphorylation (Gould and Nurse, 1989) while Cdc25 promotes entry into mitosis by removing the inhibitory phosphorylation (Gautier et al, 1991;Kumagai and Dunphy, 1991;Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%